Analysis of structural changes at interfaces of dental tissues by EDIXS and FTIR - Sánchez, Héctor Jorge; Leani, Juan Jose; Robledo, José Ignacio; Grenón, Miriam Silvina; Marcelli, Augusto Claudio; Migliori, Alessandro; Yuying Liu, Huijuan Wang; Qi, Zeming (2023)
Fil: Sánchez, Héctor Jorge. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.